The Social Consequences of Voice: An Examination of Voice Type and Gender on Status and Subsequent Leader Emergence - McClean, Elizabeth J.; Martin, Sean R.; Emich, Kyle J.; Woodruff, Col. Todd (Academy of Management Journal, 2018)
This paper explores the impact of two types of voice and gender on peer-rated social status and subsequent leader emergence. Across two studies—a three-wave field study and an experiment—we find that speaking up promotively, but not prohibitively, is positively and indirectly related to leader emergence via status, and that this relationship is conditional on the gender of the speaker. Specifically, men who spoke up promotively benefited the most in terms of status and leader emergence, not only compared to men who spoke up prohibitively, but also compared to women who spoke up promotively. This research extends our understanding of the outcomes of voice by articulating how it impacts one’s place in his or her group’s social structure, and ultimately whether he or she is seen as a leader. We also add to our understanding of leader emergence by suggesting that talking a lot or participating at a high level in a group may not be enough to emerge as a leader—it also depends how you do it and who you are.